1989
DOI: 10.1104/pp.89.2.617
|View full text |Cite
|
Sign up to set email alerts
|

Thermotolerance of Isolated Mitochondria Associated with Heat Shock Proteins

Abstract: Mitochondria isolated from 2-day-old etiolated soybean (Glycine max) seedlings which had been subjected to various heat shock treatments, i.e. (A) 280C (2 h), (B) 380C (2 h), (C) 380C (2 h)-42.50C (0.5 h), and (D) 38°C (2 h)-42.50C (0.5 h)-280C (4 h), were monitored for 02 uptake using an oxygen electrode. Mitochondria isolated after all four heat shock treatments were active in 02 consumption at 280C in response to succinate and ADP (derived P/O ratios were 1.6, 1.7, 1.3, and 1.3, respectively.) The mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…The ER, P, M, and Po sHsps have all been localized in vivo to the respective organelles and cannot be detected in the cytoplasm. Mitochondrial sHsps are reported to be involved with the protection of mitochondrial proteins during hs and with increased thermotolerance (Chou et al 1989;Liu and Shono 1999;Sanmiya et al 2004). Similarly, overexpression of the chloroplast-localized sHsp protects photosystem II under some stress conditions (Neta-Sharir et al 2005;Guo et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The ER, P, M, and Po sHsps have all been localized in vivo to the respective organelles and cannot be detected in the cytoplasm. Mitochondrial sHsps are reported to be involved with the protection of mitochondrial proteins during hs and with increased thermotolerance (Chou et al 1989;Liu and Shono 1999;Sanmiya et al 2004). Similarly, overexpression of the chloroplast-localized sHsp protects photosystem II under some stress conditions (Neta-Sharir et al 2005;Guo et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some HSPs become selectively localized in cellular organelles in a temperature-dependent fashion and relocate to the cytoplasm after a 28°C incubation period (Lin et al, 1984). Isolated mitochondria with associated HSPs are functional in oxidative phosphorylation under thermal stress, suggesting that association of HSPs with organelles provide protection from heat damage (Chou et al, 1989 (Jinn et al, 1993). In soybean, depletion of the 15-to 18-kD HSPs in the HSP-enriched fraction resulted in the loss of the thermostabilizing ability, and this ability was again restored when these HSPs were added.…”
mentioning
confidence: 99%
“…The novel 10 kDa hsp identified herein, fits these criteria and may therefore represent plant mitochondrial opal0. The identity of the 24 kDa stress protein heat induced in these studies is not known but, mitoehondrial 22 kDa and 24 kDa hsps have been observed in soybean [33]. Analysis of chloroplast proteins revealed the presence of heat shock inducible proteins with apparent MWs of 75, 72, 60, 18 and 12 kDa, respectively.…”
Section: Discussionmentioning
confidence: 99%